The The Effectiveness of Recitation Method Based on ICT (Moodle) in Learning Argumentation Writing Skills - Franscy Franscy; Leroy Holman Siahaan (Jurnal Studi Guru dan Pembelajaran, 2021)
This research is designed specifically to measure the effectiveness of recitation method based on ICT (Moodle) in learning argumentation writing skills at students of English Language Education Program, Universitas Panca Sakti Bekasi. which based on the result of preliminary observation which show that students learning outcome was still low and there were some problems that related to the result of their writing skills that still have not achieved the expected aims. This research used the method of classroom action research that involved the number of samples in this research were 30 students. For the data collecting technique, this research used quantitative data and qualitative data. Quantitative data was taken from the results of the pre-test and post-test, while qualitative data was taken during the process of observation and action. The research result shows that there is an increase in learning activity and student learning outcomes. The increase is known from the percentage value of student activity in attending learning process has increased, the results obtained in the first cycle percentage is 53%, then there is an increase in the second cycle to 55%. Student learning outcomes also increased, the average score in cycle 1 is 77.47, with the number of students completing are 21. Cycle 2 there is an increase in the average score by 4.13 to 81.6 with the number of students completing are 23.